Die digitalen Fortschrittshubs Gesundheit – Gemeinsame Datennutzung über die Universitätsmedizin hinaus - Krefting, Dagmar; Bavendiek, Udo; Fischer, Joachim; Marx, Gernot; Molinnus, Denise; Panholzer, Torsten; Prokosch, Hans-Ulrich; Leb, Ines; Weidner, Jens; Sedlmayr, Martin (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
The digital health progress hubs pilot the extensibility of the concepts and solutions of the Medical Informatics Initiative to improve regional healthcare and research. The six funded projects address different diseases, areas in regional healthcare, and methods of cross-institutional data linking and use. Despite the diversity of the scenarios and regional conditions, the technical, regulatory, and organizational challenges and barriers that the progress hubs encounter in the actual implementation of the solutions are often similar. This results in some common approaches to solutions, but also in political demands that go beyond the Health Data Utilization Act, which is considered a welcome improvement by the progress hubs. In this article, we present the digital progress hubs and discuss achievements, challenges, and approaches to solutions that enable the shared use of data from university hospitals and non-academic institutions in the healthcare system and can make a sustainable contribution to improving medical care and research.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Data integration; Digitalization; Interoperability; Intersectoral healthcare; Medicine; Patient journey